1999
DOI: 10.1046/j.1365-313x.1999.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protoporphyrinogen oxidase expression in Arabidopsis causes a lesion‐mimic phenotype that induces systemic acquired resistance

Abstract: SummaryWe have used an antisense expression technology in Arabidopsis based on the yeast GAL4/UAS transactivation system (Guyer et al., Genetics, 1998; 149:633-639) to reduce levels of protoporphyrinogen IX oxidase (PPO), the last common enzyme of the biosynthesis of the haem group and chlorophyll. Plants expressing the antisense PPO gene presented growth alterations and their leaves showed necrotic lesions that appeared similar to lesions characteristic of the pathogen-induced hypersensitive reaction, and see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 91 publications
3
67
0
Order By: Relevance
“…In contrast, the reason for the in vitro inhibition of CAT at higher concentration of SA (5 and 10 mM) and/or no inhibitory effect on APX and POX is not known and warrants further study. To explain in another way, SA is known to inhibit heme content of the plant (Molina et al, 1999). Salicylic acid-mediated inhibition of heme containing cytochromes (Cytochrome f 554 ) has been reported in our earlier study (Sahu et al, 2002).…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, the reason for the in vitro inhibition of CAT at higher concentration of SA (5 and 10 mM) and/or no inhibitory effect on APX and POX is not known and warrants further study. To explain in another way, SA is known to inhibit heme content of the plant (Molina et al, 1999). Salicylic acid-mediated inhibition of heme containing cytochromes (Cytochrome f 554 ) has been reported in our earlier study (Sahu et al, 2002).…”
Section: Discussionmentioning
confidence: 69%
“…Several previous studies reported that PPO1 mediates the plant defense response, resistance to peroxidizing herbicide, and drought tolerance (29)(30)(31). These roles of PPO1 are directly linked to the photosensitizing and oxidizing properties of porphyrins, which are synthesized in the tetrapyrrole metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of protox in Arabidopsis leads to production of lesion-mimic phenotype, high endogenous level of salicylic acid and PR1 gene expression. 90 Overexpression of plastidic protox leads to resistance to the DPE herbicide acifluorfen. The overexpressed plants did not show any necrotic leaves.…”
Section: Nadph Oxidasesmentioning
confidence: 99%